In vitro production of blastocysts in goats, sheep and buffaloes - CHAUHAN, M S; KATIYAR, P K; MADAN, M L (The Indian Journal of Animal Sciences, 2013)
This study was carried out to establish a common culture system for in vitro maturation, in vitro fertilization and in vitro roduction of goat, sheep and buffalo blastocyst embryos. Follicular oocytes of goats, sheep and buffaloes were matured in TCM-199 medium supplemented with 10% foetal bovine serum (FBS) and 5 ug/ml follicle-stimulating hormone (FSH). Some of the oocytes were stained by 2% Giemsa stain and observed for nuclear maturation and the other were fertilized with capacitated sperms. The maturation rates ranged from 65 to 78% with no signicicant difference among the species. The cleavage rates were highest in buffaloes (59%), followed by sheep (56%) and goats (41%). When these cleaved oocytes were cultured in TCM-199 medium spplemented with 10% FBS and 5 ug/ml insulin for 9 days.34% buffalo oocytes reached blastocyst stage. This was significantly higher (P<0.01)than the corresponding values in goat (8.1%) and sheep (4.7%).